Monomolecular G-quadruplex structures with inversion of polarity sites: new topologies and potentiality. Issue 14 (29th June 2017) - Virgilio, Antonella; Russo, Annapina; Amato, Teresa; Russo, Giulia; Mayol, Luciano; Esposito, Veronica; Galeone, Aldo
Abstract: In this paper, we report investigations, based on circular dichroism, nuclear magnetic resonance spectroscopy and electrophoresis methods, on three oligonucleotide sequences, each containing one 3′-3′ and two 5′-5′ inversion of polarity sites, and four G-runs with a variable number of residues, namely two, three and four (mTG2 T, mTG3 T and mTG4 T with sequence 3′-TG n T-5′-5′-TG n T-3′-3′-TG n T-5′-5′-TG n T-3′ in which n = 2, 3 and 4, respectively), in comparison with their canonical counterparts (TG n T)4 ( n = 2, 3 and 4). Oligonucleotides mTG3 T and mTG4 T have been proven to form very stable unprecedented monomolecular parallel G-quadruplex structures, characterized by three side loops containing the inversion of polarity sites. Both G-quadruplexes have shown an all- syn G-tetrad, while the other guanosines adopt anti glycosidic conformations. All oligonucleotides investigated have shown a noteworthy antiproliferative activity against lung cancer cell line Calu 6 and colorectal cancer cell line HCT-116 p53−/− . Interestingly, mTG3 T and mTG4 T have proven to be mostly resistant to nucleases in a fetal bovine serum assay. The whole of the data suggest the involvement of specific pathways and targets for the biological activity.